PEMANFAATAN CAMPURAN BUAH NANAS, AIR CUCIAN BERAS, DAN GULA SEBAGAI SUMBER KARBON PADA MEDIA PEMELIHARAAN IKAN LELE ( Clarias sp ) DENGAN SISTEM BIOFLOK - Martogi Leo Sitohang; Mirna Fitrani; Dade Jubaedah (Jurnal Akuakultur Rawa Indonesia, 2018)
ABSTRACTBiofloc technology needs carbon sources to biofloc forming. The objective of this research is the effect of pineapple,rice-washing liquid, and sugar mixture as carbon sources to the rearing media of catfish that will be  cultured with biofloc system. This reseach conducted for 30 days from April to May 2016 in the Perumahan Yusuf Halim Pondok Ijo, Jalan Lintas Timur KM 32 Indralaya, Kabupaten Ogan Ilir Provinsi Sumatra Selatan. This Research is using completely randomized design which are contained by 4 treatments and 3 replication the treatments are carbon sources from molase with C/N 15 Ratio (P0), carbon sources from mixture of pineapple, rice-washing liquid and sugar with C/N 10 Ratio (P1), C/N 15 Ratio (P2), C/N 20 Ratio (P3). The parameter are survival rate, growth, food efficiency and water quality.Keywords : Biofloc, Catfish, Pineapple, rice-washing liquid, Sugar, C/N Ratio